Mapping the Evolution Classroom to Experience: A Global Bibliometric Analysis of Experiential Learning in Physics Education - Thomas Enggar Dwi Prasetyo; I Made Astra; Teguh Budi Prayitno; Firmanul Catur Wibowo; Iwan Sugihartono (Universitas Lambung Mangkurat, 2026)
The integration of traditional classroom instruction and hands-on experience through experiential learning in physics education requires systematic mapping to understand its research development. This study aims to: (1) analyze publication trends and geographic distribution; (2) identify influential journals, authors, and collaboration networks; (3) determine dominant research themes through keyword analysis; and (4) propose future research directions. Data were retrieved from the Scopus database (2020–2025), comprising 30 sources and 54 documents. A quantitative bibliometric method was employed using RStudio with the Bibliometrix package to examine publication trends, collaboration patterns, and thematic structures. The findings show a significant increase in publications in 2024 (15 documents), with the United States contributing the largest share (64.4%). Collaboration networks remain fragmented across 14 clusters. Thematic analysis identifies “educational innovation” as a motor theme, while “physics education” appears as a basic yet relatively isolated theme. Overall, experiential learning research in physics education is growing rapidly and shows strong potential for technology integration. These findings imply that researchers, educators, and curriculum developers need to promote stronger international collaboration, develop more context-specific experiential learning models, and integrate emerging technologies to enhance the relevance and effectiveness of physics education. However, broader international collaboration and more contextualized approaches are needed to strengthen future research development.